Spontaneous recovery of effects of contrast adaptation without awareness - Mei, Gaoxing; Dong, Xue; Dong, Bo; Bao, Min (Frontiers in Psychology, 2015)
Prolonged exposure to a high contrast stimulus reduces the neural sensitivity to subsequent similar patterns. Recent work has disclosed that contrast adaptation is controlled by multiple mechanisms operating over differing timescales. Adaptation to high contrast for a relatively longer period can be rapidly eliminated by adaptation to a lower contrast (or meanfield in the present study). Such rapid deadaptation presumably causes a short-term mechanism to signal for a sensitivity increase, cancelling ongoing signals from long-term mechanisms. Once deadaptation ends, the short-term mechanism rapidly returns to baseline, and the slowly decaying effects in the long-term mechanisms reemerge, allowing the perceptual aftereffects to recover during continued testing. Although this spontaneous recovery effect is considered strong evidence supporting the multiple mechanisms theory, it remains controversial whether the effect is mainly driven by visual memory established during the initial longer-term adaptation period. To resolve this debate, we used a modified Continuous Flash Suppression (CFS) and visual crowding paradigms to render the adapting stimuli invisible, but still observed the spontaneous recovery phenomenon. These results exclude the possibility that spontaneous recovery found in the previous work was merely the consequence of explicit visual memory. Our findings also demonstrate that contrast adaptation, even at the unconscious processing levels, is controlled by multiple mechanisms.